Assessing impacts of rainfall patterns, population growth, and sea level rise on groundwater supply in the Republic of Maldives - Deng, Chenda, author; Bailey, Ryan, advisor; Grigg, Neil, committee member; Sanford, William E., committee member (Colorado State University. Libraries, 2016)
Groundwater resources of the Republic of the Maldives are threatened by a variety of factors including variable future rainfall patterns, continued population growth and associated pumping demands, rising sea level, and contamination from the land surface. The Maldives is composed of approximately 2,000 coral islands residing in 26 atolls in the Indian Ocean, with each coral island less than a few square kilometers in surface area and less than a few meters in elevation. This thesis uses numerical modeling techniques to assess the influence of variable rainfall patterns, increased pumping due to population growth, and sea level rise on fresh groundwater supply of the coral islands that comprise the Maldives. The density-dependent groundwater flow and solute transport model SUTRA (Saturated Unsaturated Transport) is used for all simulations, with the model simulating the spatial extent of the freshwater lens in the aquifer of the coral islands. The thesis first assesses changes in groundwater supply due to variable rainfall patterns in the coming decades, a key component of water resources management for the country. Using a suite of two-dimensional vertical cross-section models, time-dependent thickness of the freshwater lens is simulated for a range of island sizes (200 m to 1100 m) during the time period of 2011 to 2050, with recharge to the freshwater lens calculated using rainfall patterns provided by General Circulation Models (GCM) for the three distinct geographic regions (north, central, south) of the Maldives. Results show that average lens thickness of islands in all three geographic regions during the 2031-2050 time period is slightly greater than during the 2011-2030 time period, indicating a mild increase in future available groundwater supply under predicted conditions. Average lens thickness during 2011-2030 for islands of 200 m, 400 m, 600 m, and 1100 m width is 0.5 m, 3.0 m, 7.0 m, and 12.2 m, respectively, with these values increasing by 1-5% during 2031-2050 time period. However, these results do not include the effect of sea level rise. To quantify the total available groundwater on a representative island and to provide accurate simulation of the effect of radial pumping on the freshwater lens, a three dimensional model is created for the island of Gan (Area: 598 ha, Population: 4,280) to evaluate the impact of increasing pumping and sea-level rise on future groundwater resources. Simulations covering the 2012-2050 period are used to compare scenarios of future rainfall, pumping vs. non-pumping, varying rates of population growth and hence of groundwater pumping, and sea level rise (0.5 m by 2100) vs. no sea level rise. Results indicate that the total freshwater volume increases about 19% under the effects of future rainfall patterns. If moderate pumping is included, with rates increasing at 1.76% to correspond with increasing population, the volume increases only by 12%. If just considering sea level rise, then the volume decreases by 14%. With aggressive pumping, corresponding to an annual population growth rate of 9%, but no sea level rise, the volume decreases by 24%. With aggressive pumping and sea level rise, the freshwater lens is rapidly depleted. This study quantifies the major future impacts on groundwater of the atoll islands in Maldives. Similar methodologies using output from GCMs can be used for other atoll island nations, such as the Republic of Marshall Islands, Federated States of Micronesia, and Gilbert Islands. For the Maldives, results from this study can be used in conjunction with population growth estimates to determine the feasibility of including groundwater in water resources planning and management for the country.